Similarity solutions of isothermal flows behind a MGD blast wave in an inhomogeneous medium - Rai A.; Gaur M.; Upadhyay R.P. (My University, 2025)
Self-similar solutions of isothermal flows behind a cylindrical magnetogasdynamic blast wave have been obtained. A strong cylindrical shock wave generated by a sudden line source explosion in an inhomogeneous medium of electrically conducting gas has been studied. Numerical and analytical treatments have been presented and a uniformly valid distribution of pressure, density and velocity profiles has been determined and the magnetic-field effects on the flow distributions have been investigated. The shock propagation law is determined by extending Whitham's rule for a MGD flow with infinite electrical conductivity. © 1987 Società Italiana di Fisica.